Sistemática e filogenia do fungo parasita Escovopsis associado às formigas Attini - Meirelles, Lucas Andrade [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Attine ant nests harbor a diverse and complex microbiota. Such insects have a mutualistic relationship with mutualistic fungus, cultured as food source. However, several microorganisms are also present in attine nests. Within this microbiota, fungi in the genus Escovopsis are considered specific parasites of the mutualistic fungus. Escovopsis is only reported associated with attine ant nests. Furthermore, this parasite coevolved with attine ants and their mutualistic fungi in a tripartite relationship (tripartite coevolution model). Although several studies aimed to understand the genetic diversity of Escovopsis in Central America (mostly Panama), no comprehensive reports considering large Escovopsis samples are known from South America. There is also few taxonomic work onr this fungus; as a result, after two decades of the description of the first species, up to the present work, only six Escovopsis species have been formally described. In this study, we investigated the systematics, phylogeny and evolution of Escovopsis and separated our results in two chapters. In the first part, we describe a new species, E. kreiselii, first species belonging to basal attine ants. We also discuss the evolution of Escovopsis, indicating a correlation between phylogeny and morphological characters, where less derived strains shows absence of vesicles (structures supporting spore bearing-cells). In the second chapter, we exploit the phylogenetic diversity of Escovopsis associated with higher-attine ants in different countries of the American continent, especially Brazil. Contrary to previous resports, we show that higher attine ants share Escovopsis infections, indicating no strict co-cladogenesis between ant-cultivar-Escovopsis. The description of a new species and the extensive Escovopsis phylogeny presented here provide a first step towards a better understanding of the evolution and taxonomy of this group of fungi, which has potential for biological ...

Ninhos de formigas Attini são conhecidos por abrigar uma diversa e complexa microbiota. Esses insetos possuem uma relação de mutualismo com seu fungo simbionte, utilizado como fonte de alimento. Porém, muitos micro-organismos também são encontrados nos ninho dessas formigas. Dentre eles, destacam-se fungos do gênero Escovopsis, considerados parasitas específicos do fungo cultivado por esses insetos. Somente encontrado associado aos ninhos de formigas Attini, Escovopsis coevoluiu com as formigas e seus fungos mutualistas em uma relação tripartida. Apesar dos diversos estudos voltados para entender a variedade genética de Escovopsis realizados na América Central (especialmente Panamá), não há relatos de grandes amostragens do parasita presente na América do Sul. São também escassos trabalhos taxonômicos para esse grupo de fungo; como resultado, após mais de duas décadas da descrição da primeira espécie do gênero, até o presente trabalho, apenas seis espécies foram formalmente descritas. Nesse contexto, estudamos a filogenia e evolução de Escovopsis e separamos nossos resultados em dois capítulos. No primeiro deles, descrevemos uma nova espécie, E. kreiselii, primeira a ser descrita pertencente ao clado das formigas Attini basais. Discutimos também a evolução do fungo, indicando que parece haver correlação entre filogenia e características morfológias, com linhagens menos derivadas apresentando ausência de vesícula (célula que suporta as fiálides, produtoras de conídios). Já no segundo capítulo, exploramos a diversidade filogenética de Escovopsis associados às formigas Attini derivadas, em diferentes países do continente Americano, especialmente o Brasil. Contrariamente ao que foi previamente proposto, nossos resultados sugerem que as formigas Attini derivadas podem compartilhar linhagens de Escovopsis, indicando ausência de co-cladogênese estrita entre formiga-Escovopsis-fungo mutualista. A...
Keywords: Fungi; Fungos; Escovopsis; Formiga-cortadeira; Simbiose; Parasito